LEGAL REVIEW OF SERANG DISTRICT COURT DECISION NUMBER 187/PDT.G/2024/PN SRG IN A DISPUTE OVER BREACH OF CONTRACT REGARDING A BUSINESS CAPITAL LOAN AGREEMENT - Adit Onisyah Saputra; Bintang Al Nasha; Muasa Saputra; Muhammad Faizzar Rachman; Dede Ika Murofikoh (Hukum tata Negara/Siyasah, 2026)
Abstract:This study focuses on a legal-normative analysis of Serang District Court Decision No. 187/Pdt.G/2024/PN Srg. This study applies normative legal methodology as the main framework for examining legal issues based on applicable laws and regulations. The case examined centers on a breach of contract dispute, in which the Defendant was proven to have failed to perform its obligations under the contractual agreement. Despite the material breach of obligation, the Panel of Judges ultimately decided to dismiss the Plaintiff's claim. This decision underlines a fundamental principle in civil procedural law: the success of a breach of contract lawsuit is largely determined by the formality and integrity of the document preparation. Therefore, it is imperative for the Plaintiff to prepare the factual basis (posita) of the lawsuit in an explicit, transparent manner and in accordance with the actual facts. Keywords: Analysis, Agreement, Debt, Business Capital